2006
DOI: 10.1200/jco.2005.02.9264
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase IIα Gene Amplification Predicts Favorable Treatment Response to Tailored and Dose-Escalated Anthracycline-Based Adjuvant Chemotherapy in HER-2/neu–Amplified Breast Cancer: Scandinavian Breast Group Trial 9401

Abstract: Coamplification of HER-2/neu and TOP2A may define a subgroup of high-risk breast cancer patients who benefit from individually tailored and dose-escalated adjuvant anthracyclines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
124
0
4

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(137 citation statements)
references
References 23 publications
8
124
0
4
Order By: Relevance
“…Another recent report also showed that such post-treatment changes do exist but, as in our study, seem to be rare (Pierga et al, 2007). Whether specific molecular abnormalities can facilitate or impede response to therapy is a crucial issue in oncology (Tanner et al, 2006). However, exquisite chemosensitivity linked with specific allelic losses in tumours has not been reported yet.…”
Section: Discussionsupporting
confidence: 76%
“…Another recent report also showed that such post-treatment changes do exist but, as in our study, seem to be rare (Pierga et al, 2007). Whether specific molecular abnormalities can facilitate or impede response to therapy is a crucial issue in oncology (Tanner et al, 2006). However, exquisite chemosensitivity linked with specific allelic losses in tumours has not been reported yet.…”
Section: Discussionsupporting
confidence: 76%
“…The correlation between TOP2A gene status/topo2a protein expression and response to anthracyclines has been addressed by a legion of studies [23,26,30,[35][36][37][38][39][40][41][42][43][44][45][46][47] and are currently a matter of considerable debate. Most studies were essentially retrospective, and included breast cancer patients treated with anthracycline combinations rather than single agent anthracycline and, therefore, the activity of the other drugs of the combination could obscure any existing relationship.…”
Section: Discussionmentioning
confidence: 99%
“…137 Topo-II is a major target for anthracycline compounds, and several studies have reported TOPO-II amplification to be a better predictor of anthracycline sensitivity compared with HER-2 Mapping genetic alterations causing chemoresistance PE Lønning and S Knappskog amplifications. [138][139][140] Although experimental evidence do not suggest HER-2 overexpression to cause drug resistance, 141 interestingly, one study 142 found HER-2 overexpression to be associated with improved response when adding a taxane to anthracycline-containing chemotherapy in breast cancer patients. Finally, HER-2 activates the PI3K/akt/mTOR pathway, discussed in detail below.…”
Section: Her-2 Amplification and Chemoresistancementioning
confidence: 99%